The Effect of Foreign Debt, Liquidity, Firm Size, and Exchange Rate on Hedging Decision - Jovi Ostana Mangara Yudha; Reni Oktavia; Neny Desriani (Faculty of Economics and Business, Universitas Gadjah Mada, 2023)
Introduction/Main Objectives: This research aims to analyze the effect of internal factors, especially foreign debt, liquidity, and firm size, and also external factors, especially the exchange rate, on hedging decisions, with profitability as the control variable. Background Problems: Exchange rates are always affected by uncertainty. To ensure a company does not suffer losses, it will implement risk management, such as hedging. This is in accordance with the recommendation of the Ministry of SOEs to undertake hedging in the context of risk management. But in reality, not all state-owned enterprises do this. Novelty: This research adds profitability as a control variable, because this research does not involve the profit of the company, and focuses on how the company minimizes the risk of potential losses. Research Methods: The research used quantitative data, which is secondary data taken from the annual financial reports of state-owned enterprises listed on the Indonesia Stock Exchange for the 2016 to 2020 period that are accessed through the website www.idx.co.id and the annual reports of state-owned enterprises that are accessed through their official websites. Data analysis techniques that were used are descriptive statistics test, multicollinearity test, and logistic regression test. Finding/Results: The results show a significant effect from foreign debt and firm size on the hedging decisions of state-owned enterprises in Indonesia, while liquidity and the exchange rate did not show a significant effect on the hedging decisions of state-owned enterprises in Indonesia. Conclusion: This research shows that state-owned enterprises in Indonesia focus more on their foreign debt and firm size, than their liquidity or the exchange rate,in their decision to hedge.